Problematika Pengajar PAI Dalam Penerapan Projek Penguatan Profil Pelajar Pancasila - Agus Kurniawan, Yuski; Palupi, Aisyah Putri Dea (LP3M STIT Al Urwatul Wutsqo Jombang, 2025)
This research seeks to pinpoint the challenges encountered by PAI educators and their resolutions in executing the Pancasila Student Profile Strengthening Project (P5) at SMK PGRI Kota Pagar Alam. This research employs a qualitative descriptive methodology utilizing field research techniques. Information was gathered via observation, interviews, and documentation. The research sample consists of PAI teachers teaching in the 11th grade at SMK PGRI Kota Pagar Alam. The results of this research suggest that (1) there is a lack of understanding of P5 material due to limited training on the Merdeka Curriculum, (2) there is minimal use of interesting and relevant learning media, (3) there is low student engagement during learning activities, and (4) there are limitations in terms of human resources, facilities, and school budgets. In addressing these challenges, various solutions are proposed, including enhancing teacher training and guidance, developing more innovative teaching methods, implementing efficient classroom management, and providing full support from the school administration. These results aid in the advancement of Merdeka Curriculum implementation, particularly in integrating Pancasila values through PAI education. This study shows that the success of P5 implementation is greatly influenced by teacher readiness and school environment support.